Nursing care of a patient with head and neck squamous cell carcinoma complicated with immune-related myositis (1例头颈部鳞癌患者并发免疫相关性肌炎的护理体会) - ZHAO Jingtao (赵静涛); XIE Hongmei (解红梅); ZHANG Tong (张彤); Zhao Nan (赵楠) (Journal of International Translational Medicine Limited, 2023)
This article summarized the nursing care of a patient with head and neck squamous cell carcinoma (HNSCC) complicated with immune-related myositis. Nursing points included: nursing care on bilateral ptosis and dysphagia, the patient's safety management and psychological nursing, health education on corticosteroids therapy, etc. Trough symptomatic treatment with integrated traditional Chinese and western medicine and individual nursing care, the patient's condition was relieved, and the patient was discharged smoothly. (本总结1例头颈部鳞癌患者并发免疫相关性肌炎的护理经验。护理要点包括: 双眼睑下垂和吞咽困难的护理、安全管理和心理护理、眼周穴位按摩联合皮内针疗法、健康宣教等。通过中西医结合对症治疗以及个性化护理, 患者病情缓解并顺利出院。)